2014
DOI: 10.1084/jem.20131916
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 is a novel direct target of HIF-1α, and its blockade under hypoxia enhanced MDSC-mediated T cell activation

Abstract: Hypoxia selectively up-regulates PD-L1 on myeloid-derived suppressor cells via HIF-1a, thus affecting T cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
1,399
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,694 publications
(1,511 citation statements)
references
References 23 publications
40
1,399
3
4
Order By: Relevance
“…Hypoxia dramatically and significantly increased the percentage of PD -L1 + MDSCs isolated from the spleen in B16 -F10 and LLC tumor -bearing mice. 38 Similar results were reported by Corzo et al 39 Hypoxia via HIF -1α dramatically alters the function of MDSCs in the tumor microenvironment and redirects their differentiation toward tumor -associated macrophages, hence providing a link between different MDSCs in the tumor microenvironment. We did not identify any study concerning the relationship of hypoxia and MDSCs in humans, especially in patients with COPD.…”
Section: -32supporting
confidence: 82%
“…Hypoxia dramatically and significantly increased the percentage of PD -L1 + MDSCs isolated from the spleen in B16 -F10 and LLC tumor -bearing mice. 38 Similar results were reported by Corzo et al 39 Hypoxia via HIF -1α dramatically alters the function of MDSCs in the tumor microenvironment and redirects their differentiation toward tumor -associated macrophages, hence providing a link between different MDSCs in the tumor microenvironment. We did not identify any study concerning the relationship of hypoxia and MDSCs in humans, especially in patients with COPD.…”
Section: -32supporting
confidence: 82%
“…This ligand has been described to be expressed on MDSCs and tumor cells 20,21 and to induce T cell anergy by binding to its receptor PD-1. 22,23 In addition, we sorted recombined and non-recombined MDSCs from tumor bearing Cre-reporter mice (n D 2) and analyzed the expression of ARG-1, TGF-b and inducible nitric oxide synthase (iNOS) that play a key role in the MDSCmediated immunosuppression during the tumor progression. 20,24 The data revealed an upregulation of the expression of ARG-1 and TGF-b (to a lesser extent), suggesting the stimulation of MDSC immunosuppressive functions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S7). Other studies have reported that anti-PD-L1 treatment alone is insufficient to alter MDSC arginase activity, expression of Nos-2 or NO production (25). Only by combining anti-PD-L1 with anti-CTLA4 mAb and two epigenetic-modulating drugs were MDSC's numbers reduced (26).…”
Section: Discussionmentioning
confidence: 98%